Strategi Alokasi Dana Direktorat Mitras DUDI dalam Membangun Agenda Publik melalui Media Massa - Sirait, Nikky Partogi; Elfandari, Prisca Niken Dewi; Cahya, Muhammad Alvian (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The Directorate of Mitras DUDI was formed as a bridge that connects vocational education graduates with the business world and the industrial world. The main task is to design a vocational education revitalization policy to meet industrial needs in accordance with the challenges of the Industrial Revolution 4.0, so that vocational graduates can be directly absorbed into the world of work. To be able to establish good cooperation with the business world and the industrial world, the Mitras DUDI Directorate needs to form a good image and gain public trust. This study aims to examine the communication strategy of the Mitras DUDI Directorate in the process of agenda building through mass media, including the strategy of determining budget allocations and realizing the use of budgets based on mass media categories. The theory used is Political Branding Theory which analyzes how government institutions use mass media to form an image, and Cultivation Theory which examines the application of budget allocation preparation to distribute information massively to the public through mass media. This research is descriptive qualitative, using data collection methods in the form of interviews and literature studies. The results of this study describe the communication strategy used by the Mitras DUDI Directorate which is strengthened by the implications obtained in the field from the results of the research. The use of the right budget to convey structured and consistent information is believed to be an effective way to build a public agenda and create a good image for the Mitras DUDI Directorate.